UMA ABORDAGEM BAYESIANA PARA PREVISÃO DE RESULTADOS DE JOGOS DE FUTEBOL: UMA APLICAÇÃO AO CAMPEONATO INGLÊS - OLIVIERI FILHO, Ciro Alexandre; SUZUKI, Adriano Kamimura; LOUZADA, Francisco; SARAIVA, Erlandson Ferreira; SALASAR, Luis Ernesto Bueno (Brazilian Journal of Biometrics, 2017)
Prediction of outcomes of football matches is of great interest to fans and the press, and has been the focus of several studies in the literature. In this manuscript, we carry out an application of the Poisson regression model for the prediction of outcomes of soccer games of the 2012/2013 English Premier League under a Bayesian approach. We assume that the number of goals scored by each team in a match are independent and follow a Poisson distribution, whose average reflects the strength of the attack, defense and home advantage parameter. Before the start of each round of the second round, we calculated the win, draw and loss probabilities for each match and, through a simulation procedure, we have obtained the probability of a team qualifying for the UEFA Champions League, being crowned champion or relegated to the second division is obtained. All computer implementations were performed using WinBUGS and R systems through the R2WinBUGS package.